2015
DOI: 10.3233/rnn-140462
|View full text |Cite
|
Sign up to set email alerts
|

The motor learning induces plastic changes in dendritic spines of Purkinje cells from the neocerebellar cortex of the rat

Abstract: Since thin spines are associated with acquiring novel information whilst mushroom spines are associated with long-term information storage, there appears to be a strong relationship between AC motor learning and consolidation. The increase in stubby spines could be related to the regulation of excitatory stimulation underlying motor overactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Several types of behavioral plasticity are associated with changes in dendritic spines, the primary sites of excitatory synapses in the brain. For example, many forms of learning and memory are accompanied by dendritic spinogenesis (Moser et al, 1994;Leuner et al, 2003;Restivo et al, 2009;Vetere et al, 2011a,b;Bock et al, 2014;Kuhlman et al, 2014;Nishiyama, 2014;González-Tapia et al, 2015Mahmmoud et al, 2015;Jasinska et al, 2016;Ma et al, 2016) or spine elimination (Vetere et al, 2011b;Sanders et al, 2012;Jasinska et al, 2016;Ma et al, 2016;Swanson et al, 2017). Spine plasticity is also associated with proficiency of certain motor tasks (Fu et al, 2012;Liston et al, 2013;Hayashi-Takagi et al, 2015;Gonzalez-Tapia et al, 2016) and potentially, action-outcome expectation, given that drugs that enhance action-outcome learning can trigger spine elimination in certain brain regions (Swanson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of behavioral plasticity are associated with changes in dendritic spines, the primary sites of excitatory synapses in the brain. For example, many forms of learning and memory are accompanied by dendritic spinogenesis (Moser et al, 1994;Leuner et al, 2003;Restivo et al, 2009;Vetere et al, 2011a,b;Bock et al, 2014;Kuhlman et al, 2014;Nishiyama, 2014;González-Tapia et al, 2015Mahmmoud et al, 2015;Jasinska et al, 2016;Ma et al, 2016) or spine elimination (Vetere et al, 2011b;Sanders et al, 2012;Jasinska et al, 2016;Ma et al, 2016;Swanson et al, 2017). Spine plasticity is also associated with proficiency of certain motor tasks (Fu et al, 2012;Liston et al, 2013;Hayashi-Takagi et al, 2015;Gonzalez-Tapia et al, 2016) and potentially, action-outcome expectation, given that drugs that enhance action-outcome learning can trigger spine elimination in certain brain regions (Swanson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that memory consolidation may involve changes in the density and morphology of dendritic spines in the hippocampus, amygdala, and cerebral cortex (15)(16)(17)(18)(19)(20)(21)(22)(23). Regarding striatal spinogenesis, it has been reported that rearing rats in a rich environment produced an increase in spine density in medium spiny neurons (MSNs), which is indicative of experience-dependent neuronal modifications in this region (24,25).…”
mentioning
confidence: 99%
“…Another good candidate for contributing to postural learning is the cerebellum, which plays an important role in motor learning phenomena, such as visuomotor adaptation [77][78][79]. It has been shown that Purkinje cells undergo to significant changes in the density of their dendritic spine following an acrobatic training [80]. Indeed, the medial cerebellar vermal area controls stance [81][82][83][84][85][86] and promotes learning processes that modulates postural reflexes [63,[87][88][89][90], enhancing postural stability.…”
Section: Network Involved In the Plasticity Of Postural Functionsmentioning
confidence: 99%